Novel monoclonal antibodies against Australian strains of negeviruses and insights into virus structure, replication and host -restriction. (31st January 2020) - Colmant, Agathe M. G.; O'Brien, Caitlin A.; Newton, Natalee D.; Watterson, Daniel; Hardy, Joshua; Coulibaly, Fasséli; Bielefeldt-Ohmann, Helle; Warrilow, David; Huang, Bixing; Paramitha, Devina; Harrison, Jessica J.; Hall, Roy A.; et al.
Abstract : We report the isolation of Australian strains of Bustos virus and Ngewotan virus, two insect-specific viruses in the newly identified taxon Negevirus, originally isolated from Southeast Asian mosquitoes. Consistent with the expected insect-specific tropism of negeviruses, these isolates of Ngewotan and Bustos viruses, alongside the Australian negevirus Castlerea virus, replicated exclusively in mosquito cells but not in vertebrate cells, even when their temperature was reduced to 34 °C. Our data confirmed the existence of two structural proteins, putatively one membrane protein forming the majority of the virus particle, and one glycoprotein forming a projection on the apex of the virions. We generated and characterized 71 monoclonal antibodies to both structural proteins of the two viruses, most of which were neutralizing. Overall, these data increase our knowledge of negevirus mechanisms of infection and replication in vitro .